From A Room with a View to the Fascist Spectacle: Bloomsbury in Italy - Elena Gualtieri (Cahiers Victoriens et Edouardiens)
Many members of Bloomsbury travelled to Italy between the 1890s and the 1930s. This paper analyses Roger Fry’s, E. M. Forster’s and Virginia Woolf’s reception of Italy as a way of tracing significant changes in the social function of visual art that marked the beginnings of mass tourism and, at the same time, the emergence of the new relationship between art and politics on which Fascism was built.